TEKNIK PENCAHAYAAN BEAUTY SHOT GLOW IN THE DARK FACE PAINTING DENGAN KONSEP REOG PONOROGO - Ramanda Syah Putra; Erlina Novianti; Silviana Amanda Aurelia (Universitas Trisakti, 2023)
The Beauty Shot Glow in The Dark Face Painting Lighting Technique with Reog Ponorogo Concept. Beauty shot photography is based on the idea that everything in the photo must look beautiful, attractive, and have an aura. Face painting is a face painting process as a medium to be painted. Along with the times, face painting has experienced a creative modification in the use of paint, namely glow in the dark painting which can light up or refract its color in the dark. Glow in the dark face painting is to paint using special paint media that cannot cause irritation and damage to the skin. Besides using special paints for human skin, the type of paint used is also required to contain a mixture of phosphor substances to emit light in the dark. Glow in the dark has a similar concept to solar power because the power source is light. It aims to get the glow in the dark effect on face painting, by using low key lighting techniques. During the photoshoot, ultraviolet reflector lighting enhances the ultraviolet light emitted from the lighting to its maximum extent, aiming to bring out the glow in the dark effect on the face painting model. In this study, the authors raised the concept of Reog Ponorogo. Singo Barong is the main character in the Reog ponorogo performance and one that will be applied to the creation of the author's work. Singo Barong is a combination of Barongan and Dhadak Merak. The research method used by the author is observation, namely systematic observation by observing photo workshop of Martha Suherman. The result of creating a glow in the dark face painting artwork with the concept of Reog Ponorogo is the production of glow in the dark photos using low-key lighting techniques.Keywords: beauty shot, face painting, glow in the dark, photography, Reog Ponorogo